PELATIHAN MANAJEMEN DAYA TARIK WISATA DAN TEKNIK PEMANDUAN WISATA BAGI KELOMPOK TREKKING DI DESA BELOK SIDAN PETANG BADUNG - Sudiarta, I.N; Dewi, N.G.A.S.; Dewi, L.G.L.K.; Wijaya, N.M.S.; Sari, W.C.J. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana Mengabdi, 2018)
The purpose of community service activities are to provide knowledge to villagers Belok Sidan particularly Sadar Wisata groups and trekking group "Titi Mamah" about how to manage natural attractions and guiding techniques of trekking activities. The training uses lecture and group discussion. Aware group travel and trekking given materials to manage tourist attraction based on the quality of service and satisfaction and technique guiding that meet the expectations of tourists. The results of training activities show very enthusiastic participants attended training and various questions were raised mainly concerned with the type of products that can be sold and how a satisfactory rating on an ongoing basis.